2015
DOI: 10.1111/jpi.12235
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin regulates the autophagic flux via activation of alpha‐7 nicotinic acetylcholine receptors

Abstract: Our previous study suggested that melatonin-mediated neuroprotective effects are related with the activation of autophagy. However, the mechanism of melatonin-mediated autophagic activation in prion-mediated mitochondrial damage is not reported. Alpha-7 nicotinic acetylcholine receptors (α7nAchR) is a member of nicotinic acetylcholine receptors, and α7nAchR activation regulates via melatonin. Thus, we hypothesized that melatonin-mediated neuroprotective effect related with to autophagy pathway as a result of α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 69 publications
1
26
1
Order By: Relevance
“…Moreover, in a previous study of our group, we showed that the neuroprotective effect of melatonin against ischemia was partially mediated by alpha‐7 nicotinic receptor (α7nAchR) modulation . Related to that, Jeong et al described that melatonin regulates the autophagic flux via activation of α7nAchR, playing a pivotal role in neuroprotection of prion‐mediated mitochondrial neurotoxicity. Thus, melatonin could also be acting through α7nAchR signaling pathway to restore the autophagic flux blockade displayed by tau protein.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, in a previous study of our group, we showed that the neuroprotective effect of melatonin against ischemia was partially mediated by alpha‐7 nicotinic receptor (α7nAchR) modulation . Related to that, Jeong et al described that melatonin regulates the autophagic flux via activation of α7nAchR, playing a pivotal role in neuroprotection of prion‐mediated mitochondrial neurotoxicity. Thus, melatonin could also be acting through α7nAchR signaling pathway to restore the autophagic flux blockade displayed by tau protein.…”
Section: Discussionmentioning
confidence: 78%
“…The association between activating α7nAChR and induction of autophagy in neurons has been demonstrated. Jeong and Park reported that melatonin, a secretory hormone produced from various organs, enhanced the activation of autophagy process in neurons through the upregulation of α7nAChR signaling pathway, thus playing an important role in neuroprotection in prion-mediated neurodegenerative diseases (45). In their other article, the authors showed that the activation of α7nAChR stimulated by cellular prion protein expression contributed to the induction of autophagy flux in neurons, which played a pivotal role in neuroprotection (46).…”
Section: Discussionmentioning
confidence: 99%
“…Deleterious effects triggered by endogenous molecules or by dysfunctional processes are the basis of neurodegenerative diseases and brain tumors. Inflammatory changes, ROS and RNS formation, mitochondrial dysfunction, excitotoxicity, apoptosis, and protein aggregation are processes commonly found in these cases and related to neuron injuries [54]. …”
Section: Melatoninergic System and Neuroprotectionmentioning
confidence: 99%
“…Another interesting link between melatoninergic system and brain inflammatory responses is the regulation of the alpha-7-nicotinic acetylcholine receptors ( α 7nAchR) by melatonin [54, 6769]. Cholinergic control of inflammation adjusts the intensity of appropriate immune responses and α 7nAchR activation in immunocompetent cells shifts the immune responses towards a more anti-inflammatory profile.…”
Section: Melatoninergic System and Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation